Online Transaction Activities in an Effort to Guarantee Legal Certainty for Consumers - Yosi Esa Hadi Saputra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Development law business moment this develop with very fast. Besides that development technology is getting better proceed along with the development of the times and law should follow the development of that era. In Indonesia starting to develop a term something the so-called deed with transaction sell-buy online/online ( e-commerce ). Transaction e-commerce gives convenience for the consumer in To do activities sell-buy goods and services in accordance with the needs consumer moment it. That thing no close possibility will cause a problem law. relation with Thing that about the protection of consumers in Indonesia has set in Constitution Number 8 of 1999 concerning Protection Consumers. The article will be discussed by short how protection consumers in transaction e-commerce and how to arrange regulation related laws in the Indonesia Constitution protecting consumers as means for solving problem-related laws _ with consumers and businesses.